Le Projet urbain régénératif : un concept en émergence dans la pratique de l’urbanisme - Eduardo Blanco; Kalina Raskin; Philippe Clergeau (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Urban design practice organizes and transforms space through the development of urban projects, organizing the choices of intervention on a territory. Several initiatives in research and project practice aim to explore the integration of aspects related to the functioning of natural ecosystems in project design. Nevertheless, urbanization processes are instead a major cause of ecosystem degradation. Regenerative design proposes a better understanding of the site to guide a participatory and continuous improvement process to achieve projects with mutual positive impacts to society and ecosystems, allowing their coevolution. The implementation of regenerative design shows preliminary results internationally through various tools, but its consideration in France remains superficial. In this paper, we explore the origin and contemporary practice of regenerative design, we qualify this theory in relation to other currents of sustainable and ecological urbanism, and finally we identify the five theoretical principles of a regenerative urban project, to propose a definition to this term.